Benchmarking of electron beam parameters based on Monte Carlo linear accelerator simulation - Zhang, Fan; Zhou, Mi; Liu, Jing; Yue, Lu; Deng, Lihua; Xu, Zhijian; Wang, Gang (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2019)
Background: The main objective in this paper is to build up a simplified benchmarking procedure to determine the incident electron beam parameters independently using a Monte Carlo linear accelerator model. Methods: A 10×10 cm2 field is used to acquire the parameters influences on the dose distributions for 6 MeV megavoltage electron beams. Results: The calculated depth doses had no significant changes when the electron mean energy and radial intensity varied from 5.5–6.4 MeV and 0.1–0.4 cm respectively. And the dose profile simulated with an electron radial intensity among 0.0–0.19 cm had a good agreement with the measured dose profile in the main field, while obvious discrepancies happened in the penumbra region. The mean angular spread was found to be 0.3° to get good match between calculations and measurements at all interested depths. Conclusions: Accurate dose distributions are acquired by using the incident electron beam parameters benchmarked with the proposed procedure. As the percentage depth doses and dose profiles are insensitive to the electron energy and radial intensity correspondingly, they are feasible to benchmark individually.